PENGARUH INDEPENDENSI DAN PROFESIONALISME AUDITOR INTERNAL TERHADAP PENDETEKSIAN KECURANGAN (FRAUD) (Studi Empirik Pada PT. Semen Tonasa Kabupaten Pangkep) - Ibrahim Ibrahim (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2015)
The aim of this study was to analyze the effect of the independence of the professionalism of an internal auditor to detect fraud (fraud) in the cement company located in Sulawesi Selatan.Metode analysis is test data quality, classic assumption test, hypothesis testing, regression analysis, the coefficient determination, and significant test and test simultaneously. Based on the partial test results between the independence of the internal auditor with the detection of fraud, especially in PT. Semen Tonasa Pangkep significant and positive effect. It can be said that the more the independence of the internal auditor would be able to prevent the detection of fraud occurring within the company. Thus the hypothesis is proven. Results of regression test between the professionalism of internal auditors with the detection of fraud, which is partially no significant effect between the internal auditor's professionalism in conducting the detection of fraud that occurred in PT. Semen Tonasa Pangkep. Thus the hypothesis is proven.